The I.L. Peretz reader - Peretz, Isaac Leib, 1851 or 1852-1915 (New Yiddish library., 2002)
Isaac Leybush Peretz (1852-1915) is one of the most influential figures of modern Jewish culture. Born in Poland and dedicated to Yiddish culture, he recognized that Jews needed to adapt to their times while preserving their cultural heritage, and his captivating and beautiful writings explore the complexities inherent in the struggle between tradition and the desire for progress. This book, which presents a memoir, poem, travelogue, and twenty-six stories by Peretz, also provides a detailed essay about Peretz's life by Ruth R. Wisse. This edition of the book includes as well Peretz's great visionary drama A Night in the Old Marketplace, in a rhymed, performable translation by Hillel Halkin."If you want to discover the beauty, the depth, the unique wonder of Yiddish literature-read this volume by its Master."--Elie Wiesel"For any American reader, this will be a handy and skillfully edited selection of the most representative writings of one of the masters of world literature. For any Jewish American reader, it will also be a monument in commemoration of ... a writer who ... laid the foundations for the modern Yiddish literary tradition."-Stanislaw Baranczak, The New Republic"The tales, which occupy most of the book, vary widely. Some have the form and tone of simple folk tales. Others suggest a Hasidic-like mysticism, sometimes approaching the surreal. The best, I think combine both a sympathy for the values of the shtetl and a note of irony."-Richard Eder, Los Angeles Times Book Review"[Peretz's] works stand in brilliantly evocative tribute to a bygone era."-Publishers Weekly